2021
DOI: 10.1111/jcmm.16161
|View full text |Cite
|
Sign up to set email alerts
|

An increased burden of rare exonic variants in NRXN1 microdeletion carriers is likely to enhance the penetrance for autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is characterized by a complex polygenic background, but with the unique feature of a subset of cases (~15%‐30%) presenting a rare large‐effect variant. However, clinical interpretation in these cases is often complicated by incomplete penetrance, variable expressivity and different neurodevelopmental trajectories. NRXN1 intragenic deletions represent the prototype of such ASD‐associated susceptibility variants. From chromosomal microarrays analysis of 104 ASD individuals, we iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Recently, the largest exome sequencing study identified more than 100 high confidence ASD susceptibility genes implicated in brain development and synaptic transmission (Satterstrom et al, 2020). The genetic background of rare exonic variants in ASD susceptibility genes can also modulate the penetrance of large-effect variants, as we recently demonstrated for NRXN1 microdeletion carriers (Cameli et al, 2021). In addition, the burden of non-coding mutations has been demonstrated to contribute to the cumulative risk for ASD (Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…Recently, the largest exome sequencing study identified more than 100 high confidence ASD susceptibility genes implicated in brain development and synaptic transmission (Satterstrom et al, 2020). The genetic background of rare exonic variants in ASD susceptibility genes can also modulate the penetrance of large-effect variants, as we recently demonstrated for NRXN1 microdeletion carriers (Cameli et al, 2021). In addition, the burden of non-coding mutations has been demonstrated to contribute to the cumulative risk for ASD (Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…The related common variant burden has been shown to affect the phenotype in carriers of such variants 5 , 26 , suggesting that the cumulative effect of common variants can modify the penetrance of rare variants in such phenotypes, even when the primary cause is considered monogenic. While the impact of common variants on overall phenotypic expressivity has been examined for several neuropsychiatric 25 , 27 , 28 and other disease cohorts 29 31 , the modification of rare variant penetrance by other rare genetic variants has not been widely investigated because of the large cohort sizes required. Here, we present an analysis of common and rare variant burden in 419,854 adults from the UK Biobank (UKB) 32 .…”
Section: Mainmentioning
confidence: 99%
“…Researchers recorded an increased number of exonic rare variants in the ASD child compared to the unaffected mother. 8 One other recent study involved investigating the cognitive and behavioral skills of five children with a heterozygous NRXN1 deletion and four transmitting parents. Three of the five children were diagnosed with ASD and comorbidities, while the other two were diagnosed with an isolated intellectual disability and an unclassified neurodevelopmental disorder respectively.…”
Section: Nrxn1mentioning
confidence: 99%
“…10 The female proband with the inherited intragenic NRXN1 3p deletion exhibited a phenotype compatible with features of similar 3p deletion carriers such as dysthymic disorder (DD) and macrocephaly. 8 Epilepsy and seizures were also affiliated with heterozygous NRXN1 deletions, and three of the five children were diagnosed with intellectual disability or global developmental delay along with a major impairment in social communication skills in comorbidity with ASD. 9 NRXN2 19 rare and 1 common NRXN2 variants have been associated with ASD; the gene itself is located on chromosome 11q13.1.…”
Section: Nrxn1mentioning
confidence: 99%